Memahami Persepsi Visual: Sumbangan Psikologi Kognitif Dalam Seni Dan Desain - Margaretha Margawati van Eymeren (Universitas Multimedia Nusantara, 2014)
Perception is nature to human being. Through perception our brain organizes information from surrounding and interprets them. The process of perception can be explained scientifically by psychology that along with other branch of sciences in anthropology and philosophy can support art and design to understand their process of creativity. Bias in perception also nature, but what is nature to human being can be learnt and become a specific guidance in the process of creativity. Artists, especially, often using the nature of bias perception to precede their work.